A formação [vocal] do sujeito [contratenor] - Souza, Daniel Torri (2015)
This master thesis integrates the work of the Floema research group - Study Center for aesthetics and education - and is linked to the research line Education and Arts (LP4) Education Program Post Graduate (PPGE) of the Federal University of Santa Maria (UFSM). The research deals with the subject countertenor s vocal formation, based on the discussion of natural and unnatural use of falsetto and countertenor voice, which involves the problem of working with this vocal classification in the training of singers, especially in courses degree in Music in Brazil. To this end, we aimed to analyze the voice of countertenor and the falsetto with respect to natural and non-natural voice and its implications in the formation of singers. The specific objectives sought to identify the reasons why there is resistance to work in higher education courses in Music with the voice of countertenor and know the reasons for resistance to own work with the identification of the vocal score. The orientation of the research presents qualitative approach, based on the autobiographical approach and method. The data consisted of fragments of personal and professional career of the researcher as countertenor. Thus, a presentation and historical context about the countertenor voice and falsetto was held. To think his voice and his performance, it was based mainly on the studies of Zumthor (1993; 2005; 2010; 2014), which deal with the complex range of meanings and possibilities of the voice. Based on these studies, it was discussed what is natural and what is called unnatural voice, entering the concepts of nature and culture based on anthropological studies (Lévi-Strauss, Eribon, 1990; Lévi-Strauss, 2009; among others) and passing by studies of Looser (2005) and Linklater (2006 [1976]). These studies, added to different areas such as music, speech therapy and other voice sciences possible to understand why there is resistance to the voice of countertenor and male voice and falsetto at the very identification of the vocal classification in the researched contexts. In the process, it also problematized the very vocal training of singers, based on the understanding of voice as subjective and constitutive dimension of the subject.